Potential Habitat Modeling of Kawakawa (Euthynnus affinis) Based on Sea Surface Temperature and Chlorophyll-a Variability in the Bali Strait - Siska Wulandari; James Carter (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Kawakawa (Euthynnus affinis) distribution is strongly influenced by oceanographic variability, particularly sea surface temperature (SST) and chlorophyll-a concentration. This study models potential habitat distribution in the Bali Strait using satellite-derived SST and chlorophyll-a data. A spatial analysis approach was applied to identify habitat suitability patterns based on optimal environmental ranges. Results indicate that Kawakawa potential habitat is concentrated in waters with SST of 27–30°C and chlorophyll-a of 0.2–0.6 mg/m³. High suitability zones occur in areas with moderate thermal conditions and elevated productivity, particularly in central and northern parts of the Bali Strait. The habitat model shows strong alignment with observed fishing grounds, indicating that environmental variability effectively structures spatial distribution. These findings support the use of oceanograpqhic indicators for predicting fishing zones and improving spatial fisheries management